5-Bromo-2′-deoxyuridine Potentiation of Transformation of Rat-Embryo Cells Induced In Vitro by 3-Methylcholanthrene: Induction of Rat Leukemia Virus gs Antigen in Transformed Cells - Freeman, Aaron E. (1973)
Low-passage rat-embryo cells were not transformed by 3-methylcholanthrene or by 5-bromo-2′ deoxyuridine. However, prior treatment with bromodeoxyuridine, followed by treatment with methylcholanthrene, resulted in cell transformation about three subpassages after removal of the carcinogen. RNA-directed DNA polymerase activity could not be detected in either normal or transformed cells. However, gs-1 antigen specific for rat C-type RNA virus was detected in cultures derived from bromodeoxyuridine-treated cells. No gs-1 antigen for the C-type RNA virus was detected in cultures that had not been treated with bromodeoxyuridine during the 25 subpassages of these experiments. High-passage rat-embryo cells, derived from a different cell pool, were transformed by either methylcholanthrene or dimethylbenzanthracene without prior infection with an exogenous virus, and without prior treatment with bromodeoxyuridine, gs-1 antigen for C-type RNA virus was also detected in 4 of 4 randomly selected transformed cell lines; the gs-1 antigen was not detected in any of 4 nontransformed control cultures. Considering these and previously published findings, we conclude that the lowpassage cells cannot be transformed by methylcholanthrene because of powerful cellular controls over the endogenous virus. Bromodeoxyuridine triggers some expressions of the endogenous virus; thus, the bromodeoxyuridine-treated cells are more susceptible to the transforming effects of methylcholanthrene. High-passage rat cells do not maintain perfect control over expression of their endogenous virus; the cell cultures are susceptible to the transforming effects of chemical carcinogens.